The Role of Widyaiswara in Enhancing Educational Development in 3T Regions (Underdeveloped, Outermost, and Frontier) - Rinaldi; Veri Mei , Hafnizal (Monas: Jurnal Inovasi Aparatur, 2025)
The quality of education in underdeveloped, outermost, and frontier (3T) regions requires a more concrete contribution from Widyaiswara to support the realization of the Golden Indonesia Vision 2045. This vision urges the government to shift its development paradigm from a reformative to a transformative approach, encompassing economic, social, and governance transformation. This research was conducted from May to December 2024 using a descriptive-analytical qualitative method with a conceptual approach. The findings indicate that Widyaiswara play a crucial role in strengthening human resource capacity, particularly among educators and students, through training programs, mentoring, and educational empowerment initiatives. However, several challenges persist, including inadequate educational infrastructure, limited transportation access, and the need for more adaptive learning approaches aligned with local conditions and cultural contexts.